Contentment and Suffering Culture and Experience in Toraja - A. Kristiadji Rahardjo (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2012)
This interesting book is a result of the research conducted by Hollan and Wellenkamp in Toraja, South Celebes, 1982. It is a descriptive, person-centered ethnography of the Toraja that provides the central aspects of Toraja personal experience, including those relating to emotions, cognition, motivation, identity, and self. They also explore how and in what ways shared aspects of Toraja personal experience are related to their culture and society. This book focuses on how Toraja life is viewed and experienced from the individual’s perspective. This book provides a particularly fruitful way of conducting field research in psychocultural anthropology.